DIGITAL MULTILINGUALISM IN UZBEKISTAN: UZBEK, RUSSIAN AND ENGLISH IN ONLINE INTERACTION - Polvonniyozova, Makhliyo (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines digital multilingualism in Uzbekistan through the interaction of Uzbek, Russian, and English in online communication. The study is based on the assumption that social media, messaging platforms, comment threads, and other digital environments have become key spaces where multilingual practices are not only displayed but actively shaped. In Uzbekistan’s online sphere, the coexistence of Uzbek as the state language, Russian as a historically influential language of urban and professional communication, and English as a global language of technology, education, and digital culture creates a dynamic multilingual ecology. This study examines the main features of multilingual discourse in the digital communication environment of Uzbekistan based on a sociolinguistic and discursive approach. The study analyzes the functional distribution of languages ​​and their communicative functions using the examples of posts, comments, hashtags, advertising texts, and daily correspondence on social networks. The article also examines the hybrid language registers, transliteration, abbreviations, emojis, and the integration of English technological terms with Uzbek and Russian languages ​​under the influence of digital platforms. The results of the study show that the digital space in Uzbekistan is of great theoretical and practical importance in the study of language policy, youth speech, identity formation, and modern Internet discourse.